PERILAKU KONSUMEN COOKIES TEPUNG CASSAVA UD. NULA ABADI DI KABUPATEN BONDOWOSO - Fithroh Wahyu sulistyo Akbar; Joni Murti Mulyo Aji (UNEJ e-Proceeding, 2018)
The development of agroindustry based MSMEs can help the Indonesian economy. UD. Nula Abadi is the only MSME in Bondowoso District that processes cassava plants into flour and cookies so that it becomes a value-added product. Need the right marketing mix strategy to develop UD. Nula Abadi through analysis of consumer behavior on its customers. So the purpose of this study is to find out (1) the general characteristics of consumers and the process of purchasing decisions (2) attitudes and levels of customer satisfaction. The research method uses descriptive methods. Determination of respondents' samples with snowball sampling and judgmental sampling techniques. Data is collected by means of interviews, questionnaires, observation, literature or documentation. Data analysis using fishbein analysis, Customer Satisfaction Index, Importance Performance Analysis. The majority of consumers are women who are wives and work for civil servants. The purchase motivation comes from families and the types of opaque cookies are preferred by consumers. From the 22 attributes the results of the fishbein analysis entered the likes category. The CSI value of 88.82% is in the very satisfied category. The 4P marketing mix recommendation on products is to make innovative and distinctive products, on the place / distribution is the need to establish outlets and add agents / sales, on promotion is to use social media and direct marketing, and at prices is to use imitative pricing.